The Routledge International Handbook of Perpetrator Studies - Knittel, Susanne C.; Goldberg, Zachary J. (Routledge international handbooks, 2020)
"The Routledge International Handbook of Perpetrator Studies provides the first comprehensive overview of this emerging interdisciplinary field in the humanities and social sciences. Featuring contributions by scholars from a wide variety of fields and disciplines, the Handbook charts the growth and development, foundations, key debates, core concerns, and frontiers of Perpetrator Studies. Focusing on genocide, terrorism, and other forms of political mass violence, this Handbook addresses questions of guilt and responsibility, definition, terminology, typology, motivations, group dynamics, memory, trauma, representation, and pedagogy. Offering a thematic and conceptual approach that facilitates a comparative analysis across historical, geographic, and disciplinary lines, the Handbook allows different disciplinary perspectives to confront one another. In so doing, this foundational volume presents contemporary perspectives on longstanding debates whilst also providing new contributions to the field. Written with an interdisciplinary readership in mind, the chapters provide an overview of existing work on a specific topic or issue, delineate current developments within the respective discipline or field, and make suggestions for further research. As such, the book will appeal to scholars across a range of disciplines, including history, sociology, anthropology, criminology, law, philosophy, memory studies, psychology, political science, literary studies, film studies, cultural studies, art history, and education"-- Provided by publisher.
Keywords: 1-Histoire de l'art; 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art